Building Customer Happiness : Service Quality, Relationship Quality, and Customer Trust - Zulkifli Noor, Zulki (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study explores the impact of service quality, relationship quality, and customer trust on customer happiness. As customer satisfaction evolves into a deeper need for happiness, businesses are compelled to focus on factors that foster long-term relationships and trust with their customers. Through a quantitative approach, this research examines how service quality enhances relationship quality and trust, ultimately leading to increased customer happiness. The findings reveal a significant correlation between these variables, highlighting that customer happiness is strongly influenced by the level of trust and the quality of the relationship a customer has with a service provider. This study provides practical insights for businesses seeking to improve their service quality and build stronger relationships with customers, leading to higher levels of trust and happiness.